ENGLISH TEACHERS’ DIFFICULTIES IN DESIGNING A LESSON PLAN (RPP) BASED ON KTSP (A STUDY ON ENGLISH TEACHERS AT VOCATIONAL HIGH SCHOOLS IN BENGKULU CITY - Suci Dwina Darma; BAMBANG SUWARNO; Mulyadi Mulyadi (JOALL (Journal of Applied Linguistics and Literature), 2017)
This research aimed to find out the difficulties faced by the English teachers in Vocational High Schools in designing a lesson plan (RPP) based on KTSP. It employed a descriptive quantitative method. The population of this research was 23 respondents, from all teachers which have followed KTSP training. The sample was taken by using total sampling techniques. To collect the data, the researcher used the questionnaire. It was consist of 37 questions that it was divided into 9 aspects in a lesson plan namely; standard of competence, basic competence, indicator, the aims of learning, teaching material, the methods/techniques, the steps of learning activity, the tools/sources of material, and evaluation. It used the percentage formula and weighted mean formula to analyze data. The result of the research showed that there were not any significant difficulties in designing a lesson plan (RPP) based on KTSP faced by the English teachers in Vocational High Schools because all aspects were in sometimes/moderate predicate. It indicated that in designing a lesson plan (RPP) based on KTSP was not significant difficult. Beside that, according to the result above, the most difficult aspects were none aspect because it also with sometimes predicate. It indicated that the English teachers in Vocational High School did not find any significant difficulties in writing all aspects of the lesson plan.